2001
DOI: 10.1074/jbc.m107617200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure at 1.5-Å Resolution of Pyrus pyrifolia Pistil Ribonuclease Responsible for Gametophytic Self-incompatibility

Abstract: The crystal structure of the Pyrus pyrifolia pistil ribonuclease (S 3 -RNase) responsible for gametophytic selfincompatibility was determined at 1.5-Å resolution. It consists of eight helices and seven ␤-strands, and its folding topology is typical of RNase T 2 family enzymes. Based on a structural comparison of S 3 -RNase with RNase Rh, a fungal RNase T 2 family enzyme, the active site residues of S 3 -RNase assigned were His 33 and His 88 as catalysts and Glu 84 and Lys 87 as stabilizers of an intermediate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 53 publications
2
60
1
Order By: Relevance
“…They were found subsequently to be the hypervariable regions of Antirrhinum S-RNases as well (Xue et al, 1996) and to correspond to two of the four regions of rosaceous S-RNases for which evidence of positive selection has been found (Ishimizu et al, 1998). The crystal structures of a solanaceous S-RNase and a rosaceous S-RNase show that both HVa and HVb regions are exposed on the surface of the protein and accessible to solvent Matsuura et al, 2001). Together, HVa and HVb are considered the most likely candidates for the determinant of S-allele specificity.…”
Section: S-allele-specificity Determinant Of S-rnasesmentioning
confidence: 99%
“…They were found subsequently to be the hypervariable regions of Antirrhinum S-RNases as well (Xue et al, 1996) and to correspond to two of the four regions of rosaceous S-RNases for which evidence of positive selection has been found (Ishimizu et al, 1998). The crystal structures of a solanaceous S-RNase and a rosaceous S-RNase show that both HVa and HVb regions are exposed on the surface of the protein and accessible to solvent Matsuura et al, 2001). Together, HVa and HVb are considered the most likely candidates for the determinant of S-allele specificity.…”
Section: S-allele-specificity Determinant Of S-rnasesmentioning
confidence: 99%
“…Amino acid sequence alignment showed that SFB contained two quite variable regions, as did S-RNase (Ioerger et al, 1991;Ushijima et al, 1998). The hypervariable region of S-RNase is exposed on the surface of the folded protein molecule and plays a pivotal role in the recognition of self-pollen (Matton et al, 1997(Matton et al, , 1999Ida et al, 2001;Matsuura et al, 2001). The two variable regions of SFB at the C terminus were found to be hydrophilic enough to be exposed on the surface (data not shown) and may have important recognition functions analogous to those of the S-RNase.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of S-RNase expression by the antisense technique showed the essential role of S-RNase in the GSI reaction in apple (Broothaerts et al, 2004). The crystal structure of pear S-RNase revealed a folding topology that is typically found in RNase T 2 family enzymes (Matsuura et al, 2001). Although the biochemical function of rosaceous S-RNase is unknown, a series of immunochemical and radioactive tracer experiments with solanaceous S-RNase indicated that SRNase could function as a cytotoxin to degrade pollen RNA in an incompatible reaction.…”
Section: Pistil-s and Pollen-s Determinants In The Subfamilies Maloidmentioning
confidence: 99%
“…There is a single hypervariable region (Ushijima et al, 1998), which may form the interacting domain for GSI biochemical reactions (Matsuura et al, 2001). The function of S-RNase has been studied genetically and biochemically.…”
Section: Pistil-s and Pollen-s Determinants In The Subfamilies Maloidmentioning
confidence: 99%